PENGEMBANGAN INPUT SANTRI BARU BERBASIS ADAPTASI-KARANTINA (STUDI ANALISIS SANTRI BARU DI PESANTREN YANAABII’UL QUR’AN KUDUS) - Maragustam Siregar; Laili Nur Aini (Jurnal Pendidikan Agama Islam, 2019)
Development of new student's inputs from the beginning conducted training adapted to the Karantia system. This became significantly researched as a form of spiritual growth, knowledge, and santri skills. This research aims to answer (1) How the development of new Santri-based input of quarantine-adaptation, (2) How the forms of new students adaptation in Quarantine, and (3) How factors affecting the ability of new students adapt? Research on this field is a qualitative pedagogic approach. Subject determination using purposive and snowball sampling. Data collection using participatory observation, in-depth interviews, and documentation. Its analytical techniques use Miles and Huberman through the collection, reduction, presentation, and verification of data. The result (1) mostly new quarantine-based students being able to adapt well to specific indicators; (2) Its adaptation, adaptive with signs of physical change, social behavior, and social appeal. While the adjustive aspect with intending, value and empathy indicators. (3) The things that influence them, physiological factors, psychological, social-cultural, and maturity of individuals.